Melenyapkan Bayangan Kelam Sarkem: Upaya Rebranding Kampung Sosrowijayan Kulon melalui Kolaborasi Pemangku Kepentingan di Kampung Wisata Sosromenduran - Nugraheni, Defitri Dwi; Aprilia, Saskiawida Vita; Samara, Pingkan Aulia; Ainy, Dieny Permata (JURNAL NASIONAL PARIWISATA, 2025)
In recent years, the CBT (Community-Based Tourism) group of Sosromenduran Tourism Kampung along with the Sosromenduran Village Government and its subordinate government bodies have been striving to develop the branding of the seven kampungs it oversees. As one of the targeted kampungs, Sosrowijayan Kulon Kampung has already had its own branding due to the pre-existing presence of Sarkem (Pasar Kembang), which is widely known as a prostitution localization. Consequently, the goal was not to create a new brand from scratch but to rebrand it. This research aimed to examine the rebranding efforts of Sosrowijayan Kulon Kampung through stakeholder collaboration in Sosromenduran Tourism Kampung. A qualitative descriptive method was used with data collection through document and literature studies, observation, and semi-structured interviews with stakeholders in Sosromenduran Tourism Kampung and tourists. The research findings show that the rebranding efforts of Sosrowijayan Kulon Kampung are conducted according to stages through collaboration of various stakeholders based on pentahelix model with their respective roles, including the CBT group as initiator by encouraging community involvement and guiding in tour packages, the government as regulator and facilitator through physical and non-physical development programs, mass media as expander by disseminating information, tourism academic and consultant as conceptor through scientific publications and preparation of development program plans, and hotel and other business units as accelerator through CSR programs. Nevertheless, this collaborative effort cannot be declared successful so further actions are required.